Pectinase producing microorganism isolated from fresh and decay honeydew peel / Nurul Nazurah Ishak - Ishak, Nurul Nazurah (2017)
Pectinase is an enzyme which economically important to the enzyme industry as it helps degrade pectin, which present at the cell wall of fruit and vegetables. Microbial pectinase have been proved to provide wide uses and honeydew peel disposal is elevating in the environment. The aim of this study was to isolate and characterize pectinase producing microorganism from honeydew peel which includes bacteria and fungi. Morphology observation was performed to identify shape and Gram reaction while biochemical test was utilized to determine the enzymatic activities of the bacteria. For fungal isolates, macroscopic and microscopic examination were performed. Macroscopic observation includes color texture and surface appearance while microscopic examination includes structure of hyphae and types of spore. Pectinase screening agar medium was used for the screening of pectinase yield by the microorganism. The bacterial isolates might be from genus Bacillus sp. and Pseudomonas sp. whereas fungal isolates might be from genus Aspergillus sp.